2020
DOI: 10.1038/s41467-020-18701-4
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 trans-signaling is a candidate mechanism to drive progression of human DCCs during clinical latency

Abstract: Although thousands of breast cancer cells disseminate and home to bone marrow until primary surgery, usually less than a handful will succeed in establishing manifest metastases months to years later. To identify signals that support survival or outgrowth in patients, we profile rare bone marrow-derived disseminated cancer cells (DCCs) long before manifestation of metastasis and identify IL6/PI3K-signaling as candidate pathway for DCC activation. Surprisingly, and similar to mammary epithelial cells, DCCs lack… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 89 publications
3
34
0
Order By: Relevance
“…Thus, these clinical observations provide strong evidence of tumor dormancy in the bone marrow. However, DTCs isolated from the bone marrow of non-metastatic patients with cancer (breast, prostate, melanoma) fail to generate tumor xenografts in immunodeficient mice (364). Consequently, only tumor cell lines derived from overt metastases from patients with advanced cancer (breast, prostate) have been used in animal models to study tumor dormancy in bone (31,46,117,119,163,177,267,320,381,382).…”
Section: Mechanisms In Bone Marrow Nichesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, these clinical observations provide strong evidence of tumor dormancy in the bone marrow. However, DTCs isolated from the bone marrow of non-metastatic patients with cancer (breast, prostate, melanoma) fail to generate tumor xenografts in immunodeficient mice (364). Consequently, only tumor cell lines derived from overt metastases from patients with advanced cancer (breast, prostate) have been used in animal models to study tumor dormancy in bone (31,46,117,119,163,177,267,320,381,382).…”
Section: Mechanisms In Bone Marrow Nichesmentioning
confidence: 99%
“…In addition, independently of the hormone receptor status or breast cancer subtype, CXCL-12 triggers activation of a Src-dependent AKT signaling pathway by binding to CXCR-4, enhancing the survival of breast cancer cells in the bone marrow (387). Of note, Werner-Klein et al (364) performed single-cell RNA-sequencing analysis of DTCs isolated from the bone marrow of non-metastatic breast cancer patients (n=30 DTCs; patients) and found that mRNA expression of the IL-6 signal transducing unit gp130 (IL6ST) is strongly enriched in these cells, whereas the mRNA of the IL-6 binding receptor alpha chain CD126 (IL6RA) is absent. In the absence of CD126, the IL-6 signaling pathway can be activated in trans through the binding of IL-6 to the soluble form of CD126 (sIL6RA) prior to binding to gp130.…”
Section: Tumor Cells Interactions With Cells From Bone Marrow Nichesmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that PIK3CA variants in the single cells of bone metastases were more diverse from the variants found in the CTCs, suggesting drug refractory states may be better reflected in the heterogenous cancer cell populations in the metastases compared to CTCs. A subsequent study of TNBCs also reported the presence of pathogenic PIK3CA mutations in the malignant single cells derived from bone marrow metastases, which were absent in primary and non-metastatic tumors [27]. Targeted scDNA-seq analysis of cell-free DNA (cfDNA) and CTCs from metastatic breast cancers, found persistent heterogeneity in pathogenic variants of PIK3CA, TP53, ESR1, and KRAS genes, that were correlated with metastatic burden and prognostic implications [28].…”
Section: Genomics and Epigenomicsmentioning
confidence: 98%
“…The interactions may be direct or indirect, and the effects on CSCs include chemoresistance, preservation, and the capacity to differentiate [ 161 , 162 ]. TAMs produce cytokines including milk fat globule epidermal growth factor 8 (MFG-E8); interleukin 6 (IL-6), which can activate STAT3; and the Hedgehog signaling pathway, which seems to be one of the causes of drug resistance [ 163 , 164 ]. For example, in hepatocarcinoma, IL-6 promotes the expression of CD44+, inducing tumor development [ 165 ].…”
Section: Mechanisms Linking Cscs and Tamsmentioning
confidence: 99%